Literature Review: Diferensiasi Efek Current Ratio dan Profitability Ratio pada Harga Saham Perusahaan - Daniel Nemba Dambe; Pandu Adi Cakranegara; Deva Djohan; Irwan Moridu; Andi Hidayatul Fadlilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Financial ratios are useful for predicting a company's financial difficulties, operating results, current and future financial condition of the company, as well as a guide for investors regarding past and future performance. The current ratio and profitability ratio in the form of Return of Assets are the ratios used in the company's financial statements. The results of this report serve as a guide for investors in assessing the company so that it influences the company's stock price. The method used is a literature study by reviewing various related studies recorded in Mendeley references and Google Schoolars both nationally and internationally. The results of this study were analyzed, and used as material for discussion to determine answers to problems regarding the relationship between the current ratio and profitability ratio on the company's stock price that struggles with firm value. All ideas from each study provide information about the methodologically desirable theory of the study being analyzed. The results explain that there is a relationship between the current ratio on stock prices and return on assets can be used as a basis for determining the level of company profitability. Therefore, it is affected by the positive and significant influence between the current ratio and the profitability ratio on stock prices. Keywords: Current Ratio, Return of Assets, Profitability Ratio, Stock Price